The impact of fatigue and different environmental conditions on heart rate responses and shooting accuracy during laser run event in elite modern pentathletes - Ünver, M.; Cengizel, E.; Pekel, H. A.; Cengizel, C. Ö.; Pekel, A. Ö.; Çakir, V. O. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The final event in modern pentathlon, the laser run, determines the final ranking, and it is not known whether the athletes` heart rates (HRs) and success rates during the shooting in the laser run are affected by environmental conditions. Although heart rate (HR) affects shooting performance, exercise-induced muscle fatigue accompanying increased HR can affect shooting speed and accuracy. The aims of this research were (a) to compare the HRs of pentathletes before and after fatigue, (b) to compare the shooting performance of pentathletes in the field vs. laboratory environment, and (c) to compare the HRs of pentathletes during successful and unsuccessful shootings.